Effect of supplementation with increasing levels of probiotics on the histomorphometry of the small intestine of guinea pig (Cavia porcellus) - Puente V., Jhosseline (2019)
The present study evaluated the effect of supplementation with increasing levels of a liquid probiotic on the histomorphometry of the small intestine in guinea pigs. Fifty male guinea pigs were used from 3 days of age, distributed in a completely randomized design of five treatments with 10 repetitions each: 0, 1, 2 or 3 ml of probiotic or an antibiotic growth promoter (AGP, Zn-Bacitracin). Samples of duodenum, jejunum and ileum were taken from each animal at 84 days of age and the length and width of the intestinal villi, the depth of the Lieberkühn crypts and the length/depth relationship were measured. There were no consistent response patterns for most of the measurements in the three segments, except for a linear response (p=0.047) of the length/depth ratio in the duodenum and a positive effect (p=0.008) of the AGP over the length of villi in the ileum. It is concluded that, under the conditions of the study, the levels of the probiotic did not cause an increase in the villus dimensions and if they did, the effect was masked by an accelerated rate of cell extrusion in the villi.